Analysis of the use of the UTAUT model for modeling the information technology acceptance process - Czerwinska, Magdalena (Journal of Computer Sciences Institute, 2020)
The article is devoted to the issues of UTAUT models, which are currently the most commonly used tools of IT acceptance assessment. The aim of the article was to characterize the structure and stages of evolution of the above-mentioned models, to analyze the practical use of these models and to perform a bibliometric analysis of publications on UTAUT. The method of literature analysis and the SciVal Scopus and Google Trends tools were used to analyze UTAUT content search trend statistics. The described models are useful for testing technology acceptance by users with different characteristics in different organizations. The flexibility of the models in terms of extending and modifying them for the needs of various areas of IT technology implementation was demonstrated.